Random regression models for the prediction of days to finish in beef cattle - Speidel, Scott Eugene, author; Enns, R. Mark, advisor; Crews, Denny, committee member; Peel, R. Kraig, committee member; Hess, Ann, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: beef cattle; random regression; days to finish